Was sprach der eine zum anderen? Argumentationsformen in den sumerischen Rangstreitgesprächen - Mittermayer, Catherine (Untersuchungen zur Assyriologie und vorderasiatischen Archäologie, 2019)
Eight disputations on precedence have been preserved from Ancient Mesopotamia. In these texts, two opposing understandings of everyday life engage in a verbal argument. The works served at one time to teach oratorical competency to individuals receiving advanced literacy training. This volume examines the argumentation structure of the dialogues, thereby contributing to research on oratorical practice in the Ancient Middle East.